PEDAGÓGICA THE IMPORTANCE OF POULTRY IN EDUCATION - A NEW POLICY AND ORGANIZE EDUCATE SOCIETY FOR BRAZILIAN GINGA (Fiep Bulletin - online, 2013)
It is known that Capoeira is a sport that was included in school lessons for their socio-cultural richness. His pedagogy is organizing and educating their students, through games and songs from the african-Brazilian culture. It is a sport that favors the pedagogical aspects of education, for his liaison with the Brazilian social-historical reality. Meaning that our culture is rich and creative, both in learning how to transmit knowledge. The policy of organizing and educating society on the swings begin to show results. Shows that a part of literacy for children, can also be learned or supplied, in lessons and games of poultry occurring in a socio-cultural addition to the participants of this type. Knowledge, movement and Ginger, increasingly present in the formation of culture and sports of Brazil, which draws the attention of both Brazilian and foreign scholars, as the pedagogy of Brazilian swings. This test is characterized in the scientific methodology as a bibliographic and documentary study, conducted through a literature review and analysis of content and documents, which aims to demonstrate the importance of education and teaching capoeira in schools, gyms and clubs, for a socio-political and cultural education. For both, are presented studies of several authors on the development of the children who participate in recreational classes with poultry. Has important information and references for the improvement of professional Fitness and capoeira that practice or are involved with the sport. Introducing the dimensions of poultry training and the expected results in its practical use, through joints of poultry teaching with the teaching-learning.
Keywords: Pedagogical Capoeira; Education; Politics of Ginga